Scientific Approach Design in PAI Learning in Building Student’s Character - Nursyamsiyah, Siti; Huda, Hairul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
A scientific approach is a scientific approach. The scientific approach to teaching PAI at MI As Shofa Jember trains students' critical character to think and find solutions to problems, be honest, be creative, and be innovative. The problem in this study is the application of a scientific approach in learning PAI and the character building to be achieved in learning. The goal is to realize the character building of MI students. This study used a qualitative approach, the research subjects consisted of Islamic Religious Education teachers, school principals, vice curricula, and students. The instruments used were the observation of PAI and character learning, interviews related to learning and character building; documentation in the form of lesson plans and learning activities. The result is that the teacher applies pictures and media in the school environment. The implementation process uses 5M (observing, asking, trying, reasoning, and presenting). The 5 M learning activities in PAI learning have an impact on student character building including a) Students have high motivation to learn; b) Students become active; c) Students are able to implement in everyday life from what is seen and discussed; d) Students become diligent and disciplined; and e) Realized changes in student behavior (politeness, respect, respect, and spiritual improvement).